MATURITY, SPAWNING AND FECUNDITY OF THE KING SEER, SCOMBEROMORUS COMMERSON (LACEPEDE), IN THE SEAS AROUND THE INDIAN PENINSULA - Devaraj, M (Indian Journal of Fisheries, 2011)
Based on tlie modes of ova, 12 progressive stages are identified in the maturationof ovaries of king seer. A line, 3 standard errors above the regression ofGonad Index on total length of fish in resting or immatures stages, L (G.I. =—0.195 + 0.002046 L), is found useful in the separation of spawning flsh fromnonspawning fish. Estimation of maturity on the basis of the regression of maximumova diameter (m.o.d.) on G.t. holds only up to a G.I. of 7.2, beyond whichm.o.d. is in the range of 34 to 47 m.d. (1 m.d. = 0.0167 mm) irrespective of G.I.The length at first maturity (701-800 mm or the median 750 mm) shows considerableagreement with the values reported for the Papua New Guinea andEast African regions.